2020
DOI: 10.1088/1755-1315/492/1/012117
|View full text |Cite
|
Sign up to set email alerts
|

Selection of endophytic fungi from Sinjai local red rice as producer of IAA (Indole Acetad Acid) hormone

Abstract: South Sulawesi, specifically Sinjai area, is an aromatic rice development area that has the potential to be developed. The applied cultivation was still traditional and based on local wisdom which was without the use of fertilizers, pesticides and other chemical drugs, so it was expected that there was a high diversity of microorganism biodiversity in plant tissues, especially endophytic fungi could produce Indole Acetic Acid (IAA) hormone. The purpose of this study was studying the potential of fungi isolates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 2 publications
0
0
0
Order By: Relevance
“…The results showed that 167 isolates were IAA producers [45]. Many endophytic fungi isolated from rice and upland rice can promote the production of indoleacetic acid substances to stimulate plant growth and increase the stem length, fresh weight of stem and root, antioxidant capacity, proline, and soluble sugar content of rice plants [60,102,103] (Table 1). Note: * Antagonistic activity.…”
Section: Promotion Of Plant Hormone Secretionmentioning
confidence: 99%
“…The results showed that 167 isolates were IAA producers [45]. Many endophytic fungi isolated from rice and upland rice can promote the production of indoleacetic acid substances to stimulate plant growth and increase the stem length, fresh weight of stem and root, antioxidant capacity, proline, and soluble sugar content of rice plants [60,102,103] (Table 1). Note: * Antagonistic activity.…”
Section: Promotion Of Plant Hormone Secretionmentioning
confidence: 99%